3n+5+5n-6=

Simple and best practice solution for 3n+5+5n-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n+5+5n-6= equation:


Simplifying
3n + 5 + 5n + -6 = 0

Reorder the terms:
5 + -6 + 3n + 5n = 0

Combine like terms: 5 + -6 = -1
-1 + 3n + 5n = 0

Combine like terms: 3n + 5n = 8n
-1 + 8n = 0

Solving
-1 + 8n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 8n = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 8n = 0 + 1
8n = 0 + 1

Combine like terms: 0 + 1 = 1
8n = 1

Divide each side by '8'.
n = 0.125

Simplifying
n = 0.125

See similar equations:

| X-5/6-1=x-8/7 | | -4x+4y=-28 | | (12/7)=6y | | 11x-5+8x+90=180 | | 5(4-16)=20 | | 4x+5y=-76 | | 63x+9=-36 | | (6/7)*v=42 | | 105=23x+1+11x+2 | | 20x^4-20x^2+3=0 | | 5u+5=-10 | | 3x+5y=-67 | | 4+5m=12+3m | | 12x^3-12x^2+8=0 | | (X/15)=15 | | x+70+75+x+45=180 | | 2(x-4)=3x+32 | | 20a+13b+6c+6c-6b-4a= | | -3x-y=26 | | (y^1/8)=-1 | | 63x+9=36 | | 2t-11=15 | | -3x+3y=30 | | 15x-3=8x+16+44 | | cotg4x/cotg3x | | 8u=4v-34 | | 4x+-2y=24 | | -4x+y=-27 | | 8x=6x-10+30 | | 8x/3-8=8 | | 4h+9=33 | | 7u+5=2u-10 |

Equations solver categories